Motivation of Help to Another Person and Style Organization of Personality Life - Kyrychuk, Oleksandr (Psychological Prospects Journal, 2018)
The article is devoted to the theoretical grounding and empirical study of the interrelation between motivational characteristics of a help to another person and a life style of a personality on the example of professional group of medical nurses. The phenomenon of helping behavior of a personality has been reviewed ad its interactive nature has been determined. The motivational determination of a help to another person in external and internal characteristics of manifestation has been outlined, and the group of prosocial motives, which are connected with awareness of social importance of activity and sense of duty, has been distinguished. It has been emphasized that in individual history of human development the motivational system determines the lifestyle of a person. The conceptual use of «lifestyle» has been specified, and the need to study the life organization style for the group of assisting professions has been emphasized. The developed program of empirical research as well as the set of used methods of mathematical processing of results, gave the opportunity to concretize the theoretical positions in the form of real psychological facts: medical nurses with different levels of manifestation of help motivation demonstrate specific indicators of their life style organization, which are arranged in active regulated (average level of help manifestation, average level of facilitation potential, life styles «wheel» and «maze», «maternal» professional type and type of «sister-routiner») and active empathic (high level of manifestation of help motivation, high level of facilitation potential, life styles «stairs» and «escalator», «maternal» professional type) style life organization complexes.